Federico Neiburg y Jane I. Guyer (eds.), The Real Economy: Essays in Ethnographic Theory - Caravaca, Jimena (Prismas - Revista de historia intelectual, 2020)
Federico Neiburg y Jane I. Guyer (eds.), The Real Economy: Essays in Ethnographic Theory, Chicago, HAU Books, 2019, 299 páginas